Hypertriglyceridemia: Is there a role for prophylactic apheresis? A case report - Francisco,Ana Rita (2016)
Abstract Severe hypertriglyceridemia has been consistently associated with an increased risk of cardiovascular disease and other complications, namely acute pancreatitis. We report a case of a 64 year-old woman with hypertrophic cardiomyopathy and metabolic syndrome with triglyceride level of 3260 mg/dL. Plasma exchange was performed with simultaneous medical treatment to achieve a rapid and effective lowering of triglycerides in order to prevent clinical complications. After three plasmapheresis sessions a marked reduction in triglyceride and total cholesterol levels was observed. Several cases have shown the importance of plasmapheresis in the treatment of acute pancreatitis. We intend to demonstrate the applicability of this technique as primary prophylaxis in the presence of extremely high serum triglyceridemia levels.